Glacial geomorphology of the Notsarula and Chanchakhi river valleys, Georgian Caucasus - Levan G. Tielidze; Joanna Charton; Vincent Jomelli; Olga N. Solomina (Journal of Maps, 2023)
ABSTRACTDetailed glacial geomorphological maps are valuable for identifying target sites for palaeoglaciological reconstructions and thus for palaeoclimate inferences. In this study, we present the first detailed glacial geomorphological mapping of the landform assemblages produced by the former glaciers in the Notsarula (42°45′44″N 43°38′29″E) and Chanchakhi (42°42′5″N 43°40′42″E) river valleys, Georgian Caucasus. Our goal is to create a high-resolution (1:33,000 scale) glacial geomorphological map of this area (237 km2) and provide a detailed and accurate distribution of glacier-related features (see Main Map). Several field investigations between 2010 and 2022 along with detailed remote sensing surveys have been conducted for this glacial geomorphological mapping. The mapped landforms indicate multiple readvance or stillstands of valley glaciers across the study area. The largest and complex glacier body likely existed in the Bubistskali River gorge (42°43′16″N 43°43′32″E). Well-preserved moraine landforms in this valley suggest at least five large and several relatively small glacier readvances or stillstands occurred during the Late Quaternary. The simple-valley-type (without branches) glaciers were also probably present in other tributary valleys of the Chanchakhi River basin at that time. This map can be used for further geomorphological investigation as well as to support future geochronological work in the Greater Caucasus.